El waiver de patentes en el contexto del covid-19 por la organización mundial de comercio aproximaciones desde el derecho internacional económico - Montenegro Rubio, Pablo Xavier (2024)
This research thesis has been based on knowing the convergences maintained by the conjectures called Y for this purpose, to the Trade Related Aspects of Intellectual Property Rights, from the conjectures part of the World Trade Organization and X2 in relation to the patent waiver by the World Trade Organization in International Investment Law. For which it has been structured to analyze the construction of the Patent System, the relationship that exists between International Economic Law and Intellectual Property until determining the correlation that International Investment Law maintains through Covid 19 and its impact on Intellectual Property. That is why the results of this research study the Cronbach coefficient and the factorial analysis of variances to know if the conjectures Y are equivalent to X1 and X2, through the sample selected in the research.